Condições de otimalidade para controle ótimo via formalismo de Dubovitskii-Milyutin - Marcavillaca, Raul Tintaya [UNESP] (2016)
The purpose of this work is the study of necessary and sufficient conditions of optimality for optimal control problem including the study of the Maximum Principle and generalized convexity. The necessary conditions given by the Pontryagin Maximum Principle are obtained by means of the Dubovitski and Milyutin formalism, which allows to determine, using the language of functional analysis, necessary optimality conditions for a class of extreme problems. The sufficient conditions of optimality are given by introducing the notion of generalized invexity suitable to the problem, which we will call PM-pseudo-invexity.